1994
DOI: 10.1080/10473289.1994.10467328
|View full text |Cite
|
Sign up to set email alerts
|

Biofiltration Control of Hydrogen Sulfide 2. Kinetics, Biofilter Performance, and Maintenance

Abstract: The kinetics of H 2 S oxidation in a biofilter were evaluated and the reaction rates determined to be first-order at low concentrations (<200 ppm), zero-order at high concentrations (>400 ppm), and fractional-order in the intermediate concentration range for H 2 S in the inlet waste gas. The overall performance of the biofilter system and changes in compost properties were investigated for 200 days of operation. The compost biofiiter showed good buffering capacities to variations in gas flow rate and pollutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 4 publications
1
40
1
Order By: Relevance
“…(2) Both Hat Creek coal and Celite Biocatalyst Carrier R-635 proved to be good packing materials. However, Celite required the use of nutrient in the circulating water, whereas the coal gave good conversions without additional nutrients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Both Hat Creek coal and Celite Biocatalyst Carrier R-635 proved to be good packing materials. However, Celite required the use of nutrient in the circulating water, whereas the coal gave good conversions without additional nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Plug flow conditions in the reactors are usually assumed without further justification. [2][3][4] Lee 5 showed that the RTD of his reactor was a long way from a plug flow condition. RTD analysis of biofilter operation is a direct approach to the determination of the kinetic equations.…”
Section: Introductionmentioning
confidence: 99%
“…Biofiltration is one of the most promising clean technologies for reducing emissions of malodorous gases and other pollutants into the atmosphere (van Groenestijn andHesselink, 1993, van Groenestijn andKraakman, 2005). This technology has been proven to effectively control reduced sulfur compounds in diluted gas streams (Yang et al, 1994, Smet et al, 1998, Ergas et al, 1995, Chung et al, 1996, Devinny et al, 1999Deshusses, 2003, Kim andDeshusses, 2005). However, the elimination of H 2 S from fuel gases requires systems that can handle high loads of pollutants for extended periods of time (Maestre et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In this model, the ability of biofilters for removal of VOCs from air was described for the first time. The recent research include: Ottengraf (1986), Tiwaree, et al (1992), Shareefdeen, et al (1993), Shareefdeen and Baltiz (1994), Ergas, et al (1994), Yang and Allen (1994), Devinny (1994, 1995), Morgenroth, et al (1995), Deshusses, et al (1995a, 1995b), Tang, et al (1996), Abumaizar, et al (1997, Baltzis, et al (1997), Hwang, et al (1997), Zarook, et al (1993, 1997, Alonso, et al (1997Alonso, et al ( , 1998, Okkerse, et al (1999), and Amanullah, et al (1999) models. These models differ mainly in the following aspects: (1) model for fluid flow, (2) model for biodegradation reaction in the biofilm, (3) details of interphase transport, and (4) role of the support media (Amanullah, et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Beside organic compounds, inorganic compounds such as hydrogen sulfide and ammonia are also biodegraded well (Miller and Allen, 2004;Devinny, et al, 1999;and Swanson and Loehr, 1997). Several experimental studies were carried out to show that the removal of VOCs (Kennes and Veiga, 2004;Deshusses and Johnson, 2000;Neal and Loehr, 2000;and Mohseni and Allen, 2000), hydrogen sulfide (Busca and Pistarino, 2003;Cook, et al, 1999;Chitwood and Devinny, 1999;Shojaosadati and Elyasi, 1999;Yang and Allen, 1994;, and ammonia (Hong and Park, 2005;Martin, et al, 1996;Heslinga and Van Groenestijn, 1997; in biofilter is feasible. However, to analyze physical, chemical and biochemical phenomena occurring on biofiltration process and subsequently developing it into an optimized technology in waste treatment engineering, precise modeling of the process is required.…”
Section: Introductionmentioning
confidence: 99%